METODE PENDIDIKAN ORANG TUA BEDA AGAMA TERHADAP PERTUMBUHAN IMAN DAN IMPLIKASINYA PADA PENDIDIKAN ANAK - Roberth Edward Tabaleku; Apriana Haelitik (Sekolah Tinggi Agama Kristen Anak Bangsa, 2023)
Abstrak: Keluarga merupakan alat Tuhan untuk melaksanakan rencana-Nya. Salah satu tanggung jawab keluarga sebagai orang tua yaitu mendidik anak dalam takut akan Tuhan. Namun, masalahnya jika orang tua memiliki perbedaan agama. Perbedaan agama kedua orang tua akan mempengaruhi didikan kepada anak. Kenyataan ini menjadi tantangan bagi pihak orang tua Kristen dalam mendidik anaknya secara iman Kristen. Fokus penelitian ini tertuju pada pihak orang tua yang beragama Kristen. Tujuan penelitian ini yaitu untuk mengetahui pandangan iman Kristen mengenai pernikahan beda agama dan dampak terhadap pertumbuhan iman dan pendidikan anak. Serta memahami metode pendidikan yang dapat diterapkan pada anak untuk pertumbuhan iman dan implikasinya terhadap pendidikan anak itu sendiri. Metode kualitatif melalui tinjauan studi pustaka. Hasil yang didapat yaitu bahwa sesuai pandangan Alkitab tidak menghendaki orang percaya untuk menikah beda agama. Sebab dampak orang tua beda agama akan mempengaruhi pertumbuhan iman anak. Anak akan mengalami dilema rohani. Anak akan kehilangan identitasnya secara rohani dan akibatnya mengikuti agama lain. Anak akan kehilangan fokus dalam menyelesaikan pendidikan. Solusi yang dilakukan yaitu metode pendidikan bagi orang tua dan anak. Orang tua Kristen harus membangun hubungan yang intim dengan Tuhan, mendalami Firman Tuhan dan bersekutu dengan saudara seiman. Kemudian, orang tua harus melakukan pendekatan, menjadi teladan dan mengajarkan Firman Tuhan terus menerus kepada anak. Dengan demikian, iman anak akan mengalami pertumbuhan serta membuat fokus serta semangatnya bangkit dalam menyelesaikan pendidikannya. Abstract : Family is God's tool to carry out His plan. Therefore families need to understand the vision and mission of God for a family. One of the responsibilities of the family, in this case the parents, is to educate their children in the fear of God. However, children will get into a problem if they have parents of different religions. Because the difference in religion of the two parents will greatly affect the education they get. This also becomes the toughest challenge for Christian parents in educating their children in the Christian faith. Therefore, the focus of this research is on the parents who are Christians. The purpose of this research itself is to find out the views of the Christian faith regarding interfaith marriage and its impact on the growth of faith and children's education. As well as understanding educational methods that can be applied to children for the growth of faith and children's education. The method used is a qualitative method through a literature review by collecting information data through data collection through various reliable sources. The results obtained show that believers are not desired to marry people of different religions. Because interfaith marriages will have a huge impact not only on the family, but on the growth and education of children. So that to deal with this fact, two methods are obtained, namely the method of educating one's own faith and the method of educating children. Personally, Christian parents must be able to renew their faith first by building an intimate relationship with God and studying God's Word and allying with brothers and sisters in the faith. After that, you can apply a number of things to educate children such as approaching, setting an example and teaching God's Word continuously to children.Family is God's tool to carry out His plan. One of the responsibilities of the family as parents is to educate children in the fear of God. However, the problem is if the parents have different religions. Differences in the religion of the two parents will affect the upbringing of children. This fact is a challenge for Christian parents in educating their children in the Christian faith. The focus of this research is on the parents who are Christians. The purpose of this study is to find out the views of the Christian faith regarding interfaith marriage and its impact on the growth of faith and children's education. As well as understanding educational methods that can be applied to children for the growth of faith and the implications for the child's own education. Qualitative method through literature review. The result obtained is that according to the view of the Bible it does not want believers to marry with different religions. Because the impact of parents of different religions will affect the growth of children's faith. The child will experience a spiritual dilemma. Children will lose their identity spiritually and consequently follow other religions. Children will lose focus in completing education. The solution is an educational method for parents and children. Christian parents must build an intimate relationship with God, study God's Word and fellowship with brothers and sisters in the faith. Then, parents must approach, set an example and teach the Word of God continuously to their children. Thus, the child's faith will experience growth and make his focus and enthusiasm rise in completing his education.